Navigating 21st century industrial policy - Gary Gereffi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
New industrial policies should not aim for self-sufficiency, but rather for more secure supply chains that rely on diversified international suppliers and some domestic suppliers. Because major economies are pursuing similar goals, new industrial policies can conflict with those of friendly countries and flexibility is needed to deal with conflicts.
Keywords: 330